(3GdEHGfI aj Gdhba hGdEHJOGAs - (3eMeO Hf LYaQ Hf YHO GdcQje GdNRGYj , Qcf GdGSdGe CHh GdaVd,J (B408 (3g` s ((3CMeO Hf Ydj Hf CMeO Hf Nda GdCfUGQj GdeYQha HGHf GdHGPT s)
(3ChdgG (B:s
(3bGd GdTjN GdNRYi QVj Gddg Yfg(B: (3GdMeO ddg ENdGUkG dMeOg hJbOjekG dMbg s
(3BNQgG (B:s
(3hbGd HYVg(B: (3Ef hbaJ Ydi QCS cd BjI efgG Yf CHj YeQh hZjQg eKd Pdc ced cJGH GdEHGfI s
(3QhGjI CHj eYTQ YHOGdcQje GdebQFs
(3Yf CHj LYaQ eMeO Hf GdMSjf GdebQF GdcSGFjs
(3Yf GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs